Iconic Sites for Alpine Geology and Geomorphology - Emmanuel Reynard; Fabien Hobléa; Nathalie Cayla; Christophe Gauchon (Revue de Géographie Alpine)
In the Alps — as with the rest of Europe — renewed interest in geoheritage sites has grown since the late nineteen-nineties. Inventory, conservation and promotional (didactic, tourist) projects for geosites have blossomed at every scale — local, national and international – articulated around the central concept of geodiversity. The present article will demonstrate that far from being an entirely new tendency, this constitutes rather a specific stage in a number of different threads of the history of landscape heritage, on-going since the nineteenth century. What is new, however, is the movement that consists in basing the selection of heritage sites on their intrinsic scientific value with regard to their pertinence to the history of the Earth, rather than for any merely picturesque or aesthetic qualities. This tendency towards the implementation of geoheritage contributes to the general drive for the sustainable development of alpine territories, particularly by means of the establishment of territorial development tools such as Geoparks.